Untargeted metabolomics coupled with genomics in the study of sucrose and xylose metabolism in Pectobacterium betavasculorum - Smoktunowicz, Magdalena; Wawrzyniak, Renata; Jonca, Joanna; Waleron, Małgorzata; Waleron, Krzysztof (Frontiers in Microbiology, 2024)
Pectobacterium betavasculorum is a member of the Pectobacerium genus that inhabits a variety of niches and is found in all climates. Bacteria from the Pectobacterium genus can cause soft rot disease on various plants due to the secretion of plant cell wall degrading enzymes (PCWDEs). The species P. betavasculorum is responsible for the vascular necrosis of sugar beet and soft rot of many vegetables. It also infects sunflowers and artichokes. The main sugar present in sugar beet is sucrose while xylose is one of the main sugars in artichoke and sunflower. In our work, we applied metabolomic studies coupled with genomics to investigate the metabolism of P. betavasculorum in the presence of xylose and sucrose as the only carbon source. The ability of the strains to use various sugars as the only carbon source were confirmed by the polypyridyl complex of Ru(II) method in 96well plates. Our studies provided information on the metabolic pathways active during the degradation of those substrates. It was observed that different metabolic pathways are upregulated in the presence of xylose in comparison to sucrose. The presence of xylose enhances extracellular metabolism of sugars and glycerol as well as stimulates EPS and IPS synthesis. In contrast, in the presence of sucrose the intensive extracellular metabolism of amines and amino acids is promoted.